Implementation Of The Problem-Based Learning Approach In Improving The Quality Of Hindu Religious Learning - Casmudi (Jayapangus Press, 2020)
This study aimed to determine the implementation of the problem-based learning approach in improving the quality of Hindu religious learning, especially in high school. Less effective and efficient learning activities that tend to be monotonous were applied by educators only using conventional methods in the learning process. Students only receive learning material provided by educators, thus students were passive in learning activities and difficult in solving a problem. This resulted in unsatisfactory learning outcomes. In this case, educators must choose the right learning approach in the learning process, thus students are active and participate in solving an existing problem. The implementation of the problem-based learning approach in the Hindu religious learning process is an innovative effort and cause effective and active learning that involves students and educators solving problems together. Students must be able to learn and solve a problem as well as have the skills to solve problems involved in various situations, such as in real life